Characterization of Plasma Extrachromosomal Circular DNA in Gouty Arthritis - Pang, Jingyuan; Pan, Xiaoguang; Lin, Ling; Li, Lei; Yuan, Shuai; Han, Peng; Ji, Xiaopeng; Li, Hailong; Wang, Can; Chu, Zhaobin; Wu, Haoru; Fan, Guangyi; et al. (Frontiers in Genetics, 2022)
Objective. Extrachromosomal circular DNA elements (eccDNAs) are known for their broad existence in cells and plasma showing that they play important functions in many biological processes. Our aim was to identify potentially functional or marked eccDNAs in gout patients. Methods. Circle-Seq method was applied for eccDNA detection from plasma in acute gout patients and healthy controls. Further to analysis was performed on the distribution of genomic elements and eccDNA gene annotation in two groups. Results. 57,216 and 109,683 eccDNAs were detected from acute gout and healthy control plasma, respectively. There was no significant difference between gout and control group on genomic element annotation. A total of 256 eccDNA-associated genes were detected as gout unique eccDNA genes, including COL1A1 and EPB42, which were potentially contributing to hyperuricemia and gout, and a couple of genes involved in inflammation or immune response. Enrichment analysis showed that these eccDNA genes were highly correlated with defense response, stress response, and immune and inflammatory responses, including T cell receptor signaling pathway, Fc epsilon RI signaling pathway, and JAK-STAT signaling pathway. Conclusion. Our discovery suggests that eccDNAs in plasma lead to novel potential biological roles on gouty arthritis.